PENGARUH PROSES PEMBELAJARAN TEOREMA PYTHAGORAS DENGAN MENGGUNAKAN STRATEGI INQUIRY TERHADAP KEMAMPUAN MEMECAHKAN MASALAH SISWA KELAS VIII SMP NEGERI 14 AMBON - Patma Sopamena (IAIN Ambon, 2013)
Teaching teorema Phytagoras using inquiry strategy is an instructional model using the following steps: orientation, formulating problems, making hypothesis, collecting data, testing hypothesis, and drawing conclusion. 1) orientation aims at motivating students by presenting the instructional purpose that will be achieved and steps to achieve them, 2) formulating problems in this step, students formulate problem by considering the question given by teacher. 3) making hypothesis Students make temporary answer for the given question, 4) collecting data Students manipulate instructional media so that they can determine the length and width of each structure, 5) testing hypothesis students test the collected data, 6) drawing conclusion Students draw conclusion concerning the concept of teorema phytagoras. Kata kunci: Pembelajaran Teorema Pythagoras, Strategi Inquiry, Kemampuan Memecahkan Masalah.